The New Heretics: Skepticism, Secularism, and Progressive Christianity: Oleh Rebekka King - Gaspersz, Steve G. C. (Asosiasi Teolog Indonesia, 2024)
A book review of The New Heretics: Skepticism, Secularism, and Progressive Christianity.